What difference does it make? Exploring the transformative potential of everyday climate crisis activism by children and youth. Issue 3 (4th May 2021) - Trott, Carlie D.
ABSTRACT: Given the enormity of the climate crisis, the transformative potential of 'everyday' activism is often questioned. In this theoretical discussion, I explore the real-world significance of everyday activism by children and youth. First, I emphasize the need for top-down policy change as well as bottom-up cultural shifts. Next, I describe the significance of young people's everyday activism through the lens of countercultures, while highlighting agency-limiting practices common in present-day formal educational settings. Lastly, I call for participatory and arts-based approaches in facilitating youths' everyday climate crisis activism, noting its potential micro-level benefits and its relationship to macro-level social change.